PENGENALAN ILMU MANAJEMEN RANTAI PASOK DENGAN MODEL SIMULASI BEER GAME PADA SISWA SMK BATIK I SURAKARTA - Sri Mayasari; Nancy Oktyajati; Muhammad Fitri Budi Utomo; Ica Salsa Bila; Aland Dewayasa (Universitas Veteran Bangun Nusantara, 2024)
One of the problems faced by students at the high school/vocational high school level is confusion in choosing higher education. This is because they do not yet have an idea of the field of science and job prospects of the science that will be taken in higher education. Choosing the right study program will determine the direction of your future career, so it is necessary to introduce one of the fields of science that will be studied at the higher education level, one of which is through supply chain management. The purpose of implementing community service activities is to introduce the cluster of sciences in Industrial Engineering so that it becomes a reference for students in determining their career direction according to their interests and ideals. This community service activity was carried out using the simulation and game method with Beer Game. This activity began with a pretest, continued with a simulation, and closed with a posttest. The results of this activity showed that students had understood the basic concepts of supply chain management well. In the future, direct field activities will likely be carried out so that students' understanding of this matter becomes deeper.